Facilitators and barriers to preparing and offering whole grains to children diagnosed with prediabetes: qualitative interviews with low-income caregivers - Tashara M. Leak; Navika Gangrade; June Tester (BMC, 2021)
Abstract Background The prevalence of U.S. youth with prediabetes and type 2 diabetes (T2D) is increasing, with those from racial/ethnic minority and low socioeconomic status (SES) backgrounds at greater risk. Dietary fiber (e.g., whole grains and vegetables) is shown to be inversely associated with T2D risk, yet dietary recommendations are not being met. Caregivers play an important role in home food availability, but low SES neighborhoods are shown to have limited access to fiber-rich foods such as whole grains. The overall aim of this qualitative study was to assess caregiver perceptions about facilitators and barriers to preparing and offering whole grains that they received as part of the 16-week Food Overcoming Our Diabetes Risk (FoodRx) pilot study. Methods A convenience sample of 60 youth (8-17 years) with obesity and prediabetes were recruited from an urban pediatric weight management clinic to participate in the FoodRx pilot study. Caregivers accompanied youth to a baseline clinic visit and completed a survey that asked about individual and household characteristics. Exit interviews were conducted at the follow-up clinic visit with caregivers of all youth who completed the study (n = 48) in order to assess facilitators and barriers experienced when preparing and offering whole grains. Interview transcripts were coded using the constant comparative method and grounded theory approaches. Results Caregivers (n = 48) had a mean age of 43 years and were primarily female (n = 46) and Hispanic (71%). Main facilitators to preparing and offering whole grains in the home were caregivers' improved knowledge of whole grain health benefits and the development of strategies to encourage their children to consume whole grains (i.e., pairing whole grains with another liked food). A main barrier for caregivers was the lack of resources available to identify and prepare the novel whole grains that they received. Conclusion Findings suggest that caregivers are receptive to incorporating more whole grains into home-prepared meals, but they may need additional nutrition and cooking education to improve their self-efficacy.